Prevention of lyme disease: promising research or sisyphean task? - Krupka, Michal; Zachova, Katerina; Weigl, Evzen; Raska, Milan (Archivum immunologiae et therapiae experimentalis, 2011)
Borrelia burgdorferi sensu lato (Spirochaetes) is a group of at least 12 closely related species, some of which are responsible for chronic zoonotic infection that may cause Lyme disease. The only experimentally confirmed vector transmitting Borrelia to mammals is the Ixodes ticks. Borrelia is a highly adapted pathogen that can survive in the host organism in spite of the intense immune responses. Some patients have chronic long-lasting complications despite antibiotic therapy, probably due to adverse effects of the immune responses. A preventive vaccine against this bacterium has not been available due to the relatively broad spectrum and antigenic variability of Borrelia-surface lipoproteins and the different epitope recognition by experimental animals and humans. Although a human vaccine was marketed in the USA, it has been already pulled off the market. In addition, this vaccine was effective only in the USA, where the only pathogenic species is B. burgdorferi sensu stricto. Recent data indicate that a broadly effective vaccine will to be composed of a mixture of several antigens or multiple epitopes.
Keywords: autoimunitní nemoci; Molecular Sequence Data; protilátky bakteriální; Bacterial Outer Membrane Proteins; Ixodes; proteiny vnější bakteriální membrány; Antigens, Surface; Lipoproteins; United States; lipoproteiny; Vaccination; Mice; vakcinace; Antigenic Variation; antigeny bakteriální; Autoimmune Diseases; lymeská nemoc; Antigens, Bacterial; Borrelia burgdorferi; Bacterial Proteins; antigeny povrchové; antigenní variace; zvířata; Humans; Spojené státy americké; Antibodies, Bacterial; Bacterial Vaccines; myši; klíště; bakteriální vakcíny; Lyme Disease; molekulární sekvence - údaje; bakteriální proteiny; lidé; Animals